Manufacturing discontent: The rise to power of anti-TTIP groups - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2016)
Old beliefs, new symbols, new faces. In 2013, a small group of German green and left-wing activists, professional campaign NGOs and well-established protectionist organisations set up deceptive communication campaigns against TTIP, the Transatlantic Trade and Investment Partnership between the European Union and the United States. Germany's anti-TTIP NGOs explicitly aimed to take German-centred protests to other European countries. Their reasoning is contradictory and logically inconsistent. Their messages are targeted to serve common sense protectionist demands of generally ill-informed citizens and politicians. Thereby, anti-TTIP communication is based on metaphoric messages and far-fetched myths to effectively evoke citizens' emotions. Together, these groups dominated over 90 percent of online media reporting on TTIP in Germany. Anti-TTIP protest groups in Germany are not only inventive; they are also resourceful. Based on generous public funding and opaque private donations, green and left-wing political parties, political foundations, clerical and environmental groups, and well-established anti-globalisation organisations maintain influential campaign networks. Protest groups' activities are coordinated by a number of former and current green and left-wing politicians and political parties that search for anti-establishment political profiles. As Wallon blockage mentality regarding CETA, the trade and investment agreement between the European Union and Canada, demonstrates, Germany's anti-TTIP groups' attempts to undermine EU trade policy bear the risk of coming to fruition in other Eurpean countries. And they carry the real possibility of depriving EU Member States from new economic opportunities and economic convergence. (...)
Keywords: 330